Learn independently using the Padlet application to improve writing skills - Pakaja, Marina; Ninsiana, Widhiya; Fachruzzaki, Fachruzzaki; Yulianingsih, Lilik; Syafei, Muh (Journal International of Lingua and Technology, 2024)
This study aims to explore the effectiveness of using the Padlet application to improve writing skills through self-study. Self-directed learning methods are becoming increasingly important in today's educational landscape, with technology acting as a key driver. This study engages students in educational settings to apply independent learning using padlets in developing their writing skills. This research was conducted through a qualitative approach with a classroom action research design. Data collection was carried out through observation, interviews, and document analysis of the activities carried out by students in the learning environment. The results of the study show that the use of the Padlet application is effective in stimulating student learning independence and active participation in the development of writing skills. This app provides an interactive platform that facilitates collaboration, reflection, and feedback between students and other teachers. The results of this study have important implications for the design of learning strategies that encourage student independence and develop writing skills. In addition, this research also highlights the role of technology in creating innovative learning environments and supporting student academic growth. Thus, the application of the Padlet application in independent learning can be considered as the right solution to improve students' writing skills